Avatrombopag treatment response in patients with immune thrombocytopenia: the REAL-AVA 1.0 study - Abiola Oladapo; Scott Kolodny; Michael Vredenburg; Elyse Swallow; Debbie Goldschmidt; Kirthana Sarathy; Priscilla Lopez; Hillary Maitland; John Yee (Therapeutic Advances in Hematology, 2023)
Background: Thrombopoietin-receptor agonists (TPO-RAs) are used to treat immune thrombocytopenia (ITP), a disorder characterized by prolonged low platelet counts (PCs) that pose a risk of serious bleeding episodes. Avatrombopag (AVA) is the most recently approved TPO-RA for the treatment of chronic ITP. A high proportion of patients responded to AVA in clinical trials, and treatment was well-tolerated; however, limited real-world effectiveness data have been reported to date. Objectives: To describe demographic and clinical characteristics, treatment patterns, and outcomes following the initiation of AVA in patients with ITP in the United States. Design: This is a retrospective study using administrative claims data from the Komodo Healthcare Map (1 February 2017 to 28 February 2022) linked with PC laboratory data. Methods: Patients with ⩾1 diagnosis of ITP, ⩾1 paid prescription for AVA (index date), and ⩾1 month of pharmacy coverage after AVA initiation were selected. Baseline characteristics and follow-up steroid, immunosuppressant, and rescue medication use were described. The percentage of patients achieving clinically meaningful PC thresholds (⩾30 × 10 9 /l) were assessed among patients with ⩾1 PC following AVA initiation and prior to AVA discontinuation/switch (effectiveness subgroup). Results: A total of 205 patients met eligibility criteria and 49% reported TPO-RA use in the prior 6 months. Approximately 70% and 93% of patients did not require use of steroid or immunoglobulin rescue medication during follow-up, respectively. Among patients with concomitant steroid ( n  = 75) or immunosuppressant ( n  = 7) use at AVA initiation, 35% and 57% discontinued those treatments, respectively. Of the 21 patients in the effectiveness subgroup, 81% achieved clinically meaningful PC thresholds. Conclusion: A high proportion of evaluable patients with ITP in this real-world study achieved clinically meaningful PCs, without requiring rescue medication during AVA treatment, with many able to discontinue baseline concomitant steroid or immunosuppressant utilization. Despite limited availability of PC data, these results are consistent with results from the AVA pivotal clinical trials.